The Development and Verification of Two Time Domain Identification Algorithms Using Scientific Python Ecosystem â The Free Vibration Problems - Adriyan, Adriyan (-)
This research presented a study for verification the performance and the effectivity of identification program for modal parameters identification. The identification program was written in scientific python ecosystem by implementing Ibrahim Time Domain (ITD) and Eigensystem Realization Algorithm (ERA) method. A cantilever beam with three additional lumped masses was used as the structure under test (SUT). The SUT was modeled to produce numerically simulated responses and tested to obtain experimentally recorded responses. Especially in the first stage, the numerically simulated response was corrupted with white noise with a signal to noise ratio of 12.04 dB to imitate real vibration responses. Then, the performance was marked by capabilities to identify consecutive stable modes for every increment of model order in both stages. Both time domain method presented well those capabilities in the identification process. Hence, it can be concluded that the program can identify well even in high noise contamination in the responses and real vibration data using laboratory test scale.